"Shape-coding'': morphology-based information system for polymers and composites - Pansare, V, Amol; Chhatre, Shraddha Y.; Khairkar, Shyam R.; Bell, Jeffrey G.; Barbezat, Michel; Chakrabarti, Subhananda; Nagarkar, Amit A. (ACS Applied Materials & Interfaces, 2020)
Fiber-reinforced composites have become the material of choice for aerospace structures because of their favorable strength-to-weight ratio. Given the increasing amounts of counterfeit composite parts showing up in the complex aerospace supply chain, it is absolutely vital to track a composite part throughout its lifecycle-from production to usage and to disposal. Existing barcoding methods are invasive, affect the structural properties of composites, and/or are vulnerable to tampering. We describe a universal method to store information in fiber-reinforced composites based on solid-state in situ reduction leading to embedded nanoparticles with controlled morphologies. This simple, cost-effective, mild, surfactant-free, and one-step protocol for the fabrication of embedded platinum nanostructures leads to morphology-based barcodes for polymeric composites. We also describe a coding methodology wherein a 1 x 1 cm code can represent 3.4 billion parts to 95 trillion parts, depending on the resolution required along with access to morphology-based chemical encryption systems.
Keywords: barcoding chemical encryption; epoxy composites; nanoparticle morphology control; solid-state synthesis